2022
DOI: 10.3390/rs14163885
|View full text |Cite
|
Sign up to set email alerts
|

Urban Tree Classification Based on Object-Oriented Approach and Random Forest Algorithm Using Unmanned Aerial Vehicle (UAV) Multispectral Imagery

Abstract: Timely and accurate information on the spatial distribution of urban trees is critical for sustainable urban development, management and planning. Compared with satellite-based remote sensing, Unmanned Aerial Vehicle (UAV) remote sensing has a higher spatial and temporal resolution, which provides a new method for the accurate identification of urban trees. In this study, we aim to establish an efficient and practical method for urban tree identification by combining an object-oriented approach and a random fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 40 publications
5
25
0
Order By: Relevance
“…Our study indicated that RF had the highest classification accuracy in the three regions ( Table 5 , Table 6 and Table 7 ), which is in line with the findings of many classification studies of daytime UAV images [ 12 , 35 , 36 , 37 ]. The RF algorithm integrates multiple decision trees with good high-dimensional data processing capability and can effectively avoid noise interference.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study indicated that RF had the highest classification accuracy in the three regions ( Table 5 , Table 6 and Table 7 ), which is in line with the findings of many classification studies of daytime UAV images [ 12 , 35 , 36 , 37 ]. The RF algorithm integrates multiple decision trees with good high-dimensional data processing capability and can effectively avoid noise interference.…”
Section: Discussionsupporting
confidence: 89%
“…Of course, too much feature information can lead to redundancy. Yang K et al [ 11 ] demonstrated that differences in feature dimensionality and importance are the main factors contributing to variation in olive tree extraction accuracy; Guo Q et al [ 12 ] compared different feature combination schemes and showed that the combination by feature elimination had the highest accuracy in urban tree classification. Object-oriented approaches are often combined with machine learning in the selection of classification algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes demonstrated that the projected outcomes of the model are essentially compatible with the situation. In 2022, Guo et al [36] combined an object-oriented methodology and a random forest algorithm to provide an effective and practical method for identifying urban trees. Finally, utilising the RF, SVM, and KNN classifiers, the categorization of urban trees was carried out based on the nine methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…34,35 The RF algorithm has high computational efficiency in processing non-parametric and high dimensional data while being sensitive to overfitting. [35][36][37] The success of the RF regression model has been well-documented in recent literature. 38,39 A comparative study by Lee et al 40 assessed the performance of SVM, multiple linear regressions, and RF algorithms in predicting the canopy nitrogen content of maize.…”
Section: Introductionmentioning
confidence: 99%